PTU-072 Discontinuation of Infliximab in Patients with Ulcerative Colitis is Associated with Increased Risk of Relapse: A Multinational Retrospective Cohort Study. (17th August 2016) - Fiorino, G; Cortes, PN; Ellul, P; Felice, C; Karatzas, P; Silva, M; Lakatos, PL; Bossa, F; Sebastian, S; Ungar, B; Furfaro, F; Karmiris, K; et al.
Abstract : Introduction: Efficacy and safety of infliximab in ulcerative colitis (UC) is well-established. We conducted a multicenter retrospective cohort study across 7 European countries, and Israel, to examine whether infliximab discontinuation can be considered for patients who achieve sustained remission. Methods: The disease course of patients who discontinued infliximab was compared against that of patients who continued scheduled treatment (control group). We examined the incidence rates of relapse, hospitalisation and colectomy, the comparative effectiveness of different therapeutic strategies after discontinuation, and assessed the rates of response, remission and adverse effects after infliximab re-initiation. Statistical analyses employed time-to-event methods Results: In total, 193 patients were included, 111 discontinued infliximab. The incidence rate of relapse was significantly higher after discontinuation (23.3 per 100 person-years) as compared to the control group (7.2 per 100 person-years) both in univariable (log-rank p < 0.001; hazard ratio [HR]: 3.41, 95% CI: 1.88–6.20) and multivariable analysis (HR: 3.70, 95% CI: 2.02–6.77). Rates of hospitalisation and colectomy were not different between the groups. Thiopurines appeared to be the best treatment option after infliximab discontinuation (incidence of relapse: 15.0 per 100 person-years for thiopurines, 27.4 per 100 person-years for thiopurines plus aminosalicylates, and 31.2 per 100 person-years for aminosalicylates alone, log-rank p = 0.032). Response was regained in 77.1% and remission in 51.4% of patients who re-initiated infliximab. However, 17.1% suffered infusion reactions, and 17.1% reported other adverse events Conclusion: Infliximab discontinuation in UC patients with sustained clinical remission is associated with increased risk of relapse. Treatment re-initiation is effective and safe. Disclosure of Interest: G. Fiorino Consultant for: MSD, AbbVie, Takeda, Janssen, Mundipharma, Sandoz, Pfizer, P. Cortes: None Declared, P. Ellul Grant/research support from: MSD, AbbVie, C. Felice Consultant for: MSD, AbbVie, P. Karatzas: None Declared, M. Silva: None Declared, P. Lakatos Grant/research support from: MSD, AbbVie, Hospira, Consultant for: MSD, AbbVie, Celltrion, EGIS, Falk Pharma GmbH, Ferring, Genentech, Hospira, F. Bossa Consultant for: MSD, Abbvie, Mundipharma, and Takeda, S. Sebastian Grant/research support from: MSD, AbbVie, Speaker bureau with: MSD, B. Ungar: None Declared, F. Furfaro: None Declared, K. Karmiris Consultant for: MSD, AbbVie, Takeda, K. Katsanos: None Declared, M. Muscat: None Declared, D. Christodoulou: None Declared, G. Maconi: None Declared, U. Kopylov Consultant for: Janssen, Abbvie, Takeda and CTS, F. Magro: None Declared, G. Mantzaris: None Declared, A. Armuzzi Grant/research support from: MSD, Consultant for: Abbvie, Celltrion, Ferring, Hospira, Janssen, Lilly, MSD, Mundipharma, Pfizer, Sofar, Takeda, M. M. Boscà-Watts: None Declared, S. Ben-Horin Grant/research support from: AbbVie and Celltrion, Consultant for: AbbVie, Celltrion, Janssen, Takeda and Schering-Plough, S. Bonovas: None Declared, S. Danese Consultant for: Schering-Plough, Abbott Laboratories, Merck, UCB-pharma, Ferring, Cellerix, Millenium Takeda, Nycomed, Pharmacosmos, Actelion, Danone, Alpha Wasserman, Genentech, Grunenthal, Pfizer, Astra Zeneca, Novo Nordisk, Cosmo Pharmaceuticals, Vifor, and Johnson & Johnson, Speaker bureau with: Schering-Plough, Abbott Laboratories, Merck, UCB-pharma, Ferring, Cellerix, Millenium Takeda, Nycomed, Pharmacosmos, Actelion, Danone, Alpha Wasserman, Genentech, Grunenthal, Pfizer, Astra Zeneca, Novo Nordisk, Cosmo Pharmaceuticals, Vifor, and Johnson & Johnson